PENERAPAN COOPERATIVE LERARNING (CL) TIPE STAD UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR EKONOMI SISWA KELAS XI IIS UNGGULAN MAN II MATARAM, 2017/2018 - Aziz Aziz (Sekolah Tinggi Agama Islam AL Aqidah Al Hasyimiyyah Jakarta, 2018)
This research is a classroom action research conducted in two cycles that aims to find out the improvement of motivation and economic learning outcomes of students of class XI IIS Unggulan the odd semester of 2017/2018 in MAN 2 Mataram and the research’s subjects are all students of class XI IIS, amounted to 36 people. The test results were analyzed by using descriptive statistics. The results of this study indicate that the average student's learning motivation score 70 on cycle I with 50 % classical completeness, while in cycle II average score of 80 with 86 % classical completeness. The result of this study in the aspect of concept comprehension or written test in cycle I average by result of learning equal to 73 and classical completeness equal to 77 % (not yet completed by classical), then increase in cycle II obtained average of learning result equal to 85 and classical completeness equal to 89% (complete). In this study can be concluded that there is an increase in motivation and student learning outcomes class XI IIS Unggulan odd semester of year 2017/2018 MAN 2 Mataram through the implementation of Cooperative Learning (CL) type STAD.